Uncovering Determinants of Entrepreneurial Behaviour in a Transitioning Economy: A Fuzzy-set Qualitative Comparative Analysis - Rebean AI-Silefanee; Niels Bosma
The purpose of this research article is to explore the determinants of entrepreneurial behaviour among university students in the Kurdistan Region of Iraq. The study uses a novel approach of fuzzy-set qualitative comparative analysis (fsQCA) to depart from traditional assumptions that causal mechanisms apply equally to all individuals within a group. The study examines how shared characteristics may influence entrepreneurial behaviour. The study contributes to the theory of planned behaviour (TPB) literature by identifying different configurations of factors that lead to entrepreneurial behaviour. The study finds that these configurations vary depending on the student$1 (Bs gender, personal valuation of entrepreneurship, self-evaluation, and perceived support from their environment. These findings suggest that the context in which students are situated plays a crucial role in shaping their entrepreneurial behaviour, highlighting the importance of considering within-sample variations when studying entrepreneurial intentions. This research article uses a novel approach, fsQCA, to explore the factors that influence entrepreneurial behaviour. It departs from traditional assumptions that the same causal mechanisms apply to all individuals within a group, and instead examines how shared characteristics may influence entrepreneurial behaviour.s